Mechanisms of protecting the institutional system in Poland - Sukiennik, Jakub (Ekonomia i Prawo. Economics and Law, 2023)
Motivation: Introducing changes in the formal part of the institutional system is a process subject to certain regulations in Poland. These rules are present at the ex-ante stage of the preparation of a draft normative act, and they consist of, inter alia, the procedure for Regulatory Impact Assessment (RIA) or the so-called legislative drafting principles; furthermore, they are present at the ex-post stage of the introduction of a normative act, which can also be noticed as part of certain RIA elements and of the activities of the Constitutional Tribunal (CT). The objectives of these procedures are indirectly related to the attempt to streamline the functioning of the institutional system, which affects many entities and elements, including, for example, economic development. In addition, the quality of the regulatory environment is one of the fundamental dimensions of the functioning of the state, and the identified elements are intended to result in the creation of necessary and beneficial regulations. With a total of 5,531 acts passed in Poland from 1991 to 28 June 2022, studies of institutional system protection mechanisms indicate their low effectiveness. Aim: This article attempts to defend the thesis that ex-ante and ex-post types of institutional system protection mechanisms in Poland are only partially effective. Results: The article identifies measures to protect against ex-ante and ex-post distortions in the functioning of the institutional system in Poland. The article attempts to defend the thesis that these mechanisms are not fully effective.